The study of genetic diversity of Daemonorops draco (Palmae) using ISSR markers (Biodiversitas Journal of Biological Diversity, 2014)
Asra R, Syamsuardi, Mansyurdin, Witono JR. 2014. The study of genetic diversity of Daemonorops draco (Palmae) using ISSR markers. Biodiversitas 15: 109-114. The genetic diversity in five populations of Daemonorops draco (Willd.) Blume (Jernang: in Bahasa Indonesia) was analyzed using Inter Simple Sequence Repeat (ISSR) markers. The screening results from using 15 ISSR primers showed that only 5 of ISSR primers had clear and reproducible bands. Based on the data from the matrix binary analyzed using POPGENE version 3.2, the highest genetic diversity was found in the Sepintun population at 0.0969 average heterozygosis (H) and 0.146 average Shannon Index (I). The heterozygosis calculation of the total population (HT) was 0.2571. The heterozygosis value within a population (HS=0.0704) was smaller than that between populations (DST=0.1867). Using the clustering analysis program Pastversion 32 on 43 individuals of D. draco, we found that there were three groups of D. draco. Group A consisted of 8 individuals in the Bengayoan population, group B consisted of 9 units in the Nunusan population and group C consisted of three populations; Tebo, Sepintun and Mandiangin consisted of 10, 8 and 8 individuals. The genetic similarity varied among all populations with the values between 0.07-0.93.
Keywords: Daemonorops draco, genetic diversity, ISSR marker